Step-by-step explanation
we need to isolate the angle, so
Step 1
![\tan ^2\beta=1](https://img.qammunity.org/2023/formulas/mathematics/college/okybisswshm97wnas4rg76u3yl8sgo4gvi.png)
get the square root in both sides
![\begin{gathered} \tan ^2\beta=1 \\ √(\tan^2\beta)=√(1) \\ \tan \text{ }\beta=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g4tciny7f4o8mern3d2e1z54pinq1v6zd7.png)
Step 2
now, to isolate the angle we need to get the inverse tan in both sides
![\begin{gathered} \tan \text{ }\beta=1 \\ \tan ^(-1)(\tan \text{ }\beta)=\tan ^(-1)(1) \\ \beta=45 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tp1pyhrbb4mbcw5cgbtmz8vkq1jvwb8fui.png)
*in step 1 the tan of the angle equals -1 as well, but this solution leads to the thir
x